Investigation and Countermeasure Research on the Current Situation of Children's Swimming Training in Xi'an High-tech Zone during Summer Vacation - Lu, Hongna (International Journal of Social Sciences and Public Administration, 2025)
Conduct a survey on the current situation of the summer children's swimming training industry in Xi'an High tech Zone through methods such as literature review, on-site investigation, and questionnaire survey, in order to understand the basic situation, business models, and water quality safety of venues related to the summer children's swimming training industry in Xi'an High tech Zone; The current status of coaches' gender and age, professional titles and educational qualifications, and sources; The current situation of teaching content and assessment related to swimming teaching. Based on the current situation, we understand the problems in the summer swimming training for children in Xi'an High tech Zone, and propose relevant suggestions based on the existing problems, providing reference for the sustainable development of the summer swimming training industry for children in Xi'an.